Examining the Impact of Food Quality and the Role of Lovemarks on Brand Loyalty: Case of Coffee Shop In Indonesia - Manalu, Markus Calvin; Sobari, Nurdin (Jurnal Pendidikan Indonesia, 2025)
The increasing popularity of local coffee has led to a rise in the consumption of local coffee and the expansion of local coffee shop chains. This trend is particularly evident in Indonesia, where coffee drinking has become an ingrained cultural practice, contributing to the growth in local coffee consumption and production. This study concentrates on a leading Indonesian local coffee shop chain that has seen substantial expansion across Southeast Asia. The aim of this research is to examine the impact of food quality and the influence of lovemarks on customer brand loyalty in a prominent Indonesian coffee shop. Data for this study was gathered from 260 individuals who had consumed coffee in the previous month. The research utilized Structural Equation Modeling (SEM) through SmartPLS software for data analysis. The findings indicate that lovemarks, encompassing brand love and brand respect, positively influence brand loyalty. Additionally, factors such as healthiness, customization, price fairness, and intimacy are positively correlated with brand loyalty. Elements like healthiness, mystery, sensuality, and intimacy are positively associated with brand love. Trust, reputation, and performance positively impact brand respect. Furthermore, aspects such as hygiene and nutrition disclosure positively influence food healthiness.